(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
The influence of large-scale unloading of soil on existing metro tunnels is a difficult problem in the operation of Metro in sandy gravel strata. In order to predict and control the tunnel deformation and ensure the safety and normal operation of the metro, three-dimensional numerical models are proposed in this study. These models based on the line 5 of Chengdu subway engineering and the adjacent unloading projects analyse the deformation and stress characteristics of existing metro tunnels under large-scale unloading of soil. In conclusion, after comprehensive reinforcement measures such as advanced tubal curtains and horizontal beams, anti-floating anchor cables, the elastic modulus of strata is improved to a certain extent, and the rebound of pit bottom soil is effectively reduced. After the excavation of the foundation pits are completed, the maximum longitudinal uplift of left and right tunnel is 8.33 mm and 9.56 mm under reinforced condition, which is less than the control standard value of 10 mm.